Achieving Comprehensive Cyber Resilience: Integrating Compliance Frameworks and AI in Emerging Technologies - Marapu, Nikhileswar Reddy (International Journal of AI, BigData, Computational and Management Studies, 2023)
The exponential growth of emerging technologies such as blockchain and quantum computing has revolutionized innovation but has also introduced unprecedented cybersecurity challenges. These technologies, while transformative, are increasingly targeted by sophisticated cyberattacks that exploit their unique vulnerabilities, such as smart contract flaws and quantum threats to cryptographic systems. To ensure the resilience of these innovations, integrating artificial intelligence (AI) with compliance frameworks offers a promising solution. AI-driven tools can enhance threat detection, automate compliance processes, and enable real-time monitoring, thereby fortifying cyber defenses. This paper examines the critical role of AI in augmenting compliance frameworks to address the cyber risks associated with blockchain and quantum computing. It further explores the synergy between AI and regulatory frameworks, proposing a conceptual model for achieving comprehensive cyber resilience. This integrated approach underscores the importance of adaptive strategies to safeguard future innovations